2020
DOI: 10.1111/obr.13011
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of the effect of Roux‐en‐Y gastric bypass and sleeve gastrectomy on remission of type 2 diabetes: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Bariatric surgery is an effective treatment option for patients with type 2 diabetes mellitus (T2DM) and obesity. This study aims to compare the effects of Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) on remission of T2DM. MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials weresearched for studies published between database inception and 21 November 2019.A meta-analysis, using a random effects model, was performed to calculate relative risk (RR) of T2DM remission between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 59 publications
1
33
1
3
Order By: Relevance
“…The Fourth Global International Federation for the Surgery of Obesity (IFSO) Registry in 2018 reported that of the 190,177 primary metabolic operations, sleeve gastrectomy (SG) was the most common (87,467; 46.0%) followed by Roux-en-Y gastric bypass (RYGB) (72,645; 38.2%) and one-anastomosis gastric bypass (OAGB) (14,516; 7.6%) [ 18 ]. Previously published standard pairwise meta-analyses have produced inconsistent findings [ 19 22 ]. With the evolution of procedures and the increasing use and understanding of one-anastomosis gastric bypass [ 23 ], an updated comparative efficacy assessment is required to aid healthcare decision making.…”
Section: Introductionmentioning
confidence: 99%
“…The Fourth Global International Federation for the Surgery of Obesity (IFSO) Registry in 2018 reported that of the 190,177 primary metabolic operations, sleeve gastrectomy (SG) was the most common (87,467; 46.0%) followed by Roux-en-Y gastric bypass (RYGB) (72,645; 38.2%) and one-anastomosis gastric bypass (OAGB) (14,516; 7.6%) [ 18 ]. Previously published standard pairwise meta-analyses have produced inconsistent findings [ 19 22 ]. With the evolution of procedures and the increasing use and understanding of one-anastomosis gastric bypass [ 23 ], an updated comparative efficacy assessment is required to aid healthcare decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published network meta-analysis on diabetes remission after bariatric surgeries shows that in the follow-up over 3 years of length after LSG, the diabetes remission rate is on the level of 39.9% [ 33 ]. Moreover, the latest published systematic review of literature shows that there is no significant difference between diabetes remission in 2- to 5-year follow-up between RYGB and LSG (50% vs 45%, 95% CI (0.94–1.20)) [ 34 ]. This data however is hard to interpret due to combining 2- to 5-year follow up in one analysis—overall 5-year follow-up diabetes remission results are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, randomised controlled trials (RCTs) [1][2][3][4][5], systematic reviews, meta-analyses [6,7] and international guidelines [8][9][10][11] have indicated the benefits of bariatric-metabolic surgery for patients with type 2 diabetes mellitus (T2DM) and severe obesity compared to medical therapy alone. 'Bariatric' surgery that produces weight loss overlaps with 'metabolic' or 'diabetes' surgery where the aim is to improve conditions such as T2DM [12].…”
Section: Introductionmentioning
confidence: 99%